2019
DOI: 10.1016/j.redox.2019.101260
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia sensitive SLC4A11 mitochondrial uncoupling reduces glutamine induced oxidative stress

Abstract: SLC4A11 is a NH 3 sensitive membrane transporter with H + channel-like properties that facilitates Glutamine catabolism in Human and Mouse corneal endothelium (CE). Loss of SLC4A11 activity induces oxidative stress and cell death, resulting in Congenital Hereditary Endothelial Dystrophy (CHED) with corneal edema and vision loss. However, the mechanism by which SLC4A11 prevents ROS production and protects CE is unknown. Here we demonstrate that SLC4A11 is localized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
90
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(97 citation statements)
references
References 49 publications
7
90
0
Order By: Relevance
“…Studies from our lab and others have identified mitochondrial ROS to be the major cause of cell death in KO MCECs 5,6 . In addition, mitochondrial ROS can also cause lysosomal dysfunction and ER stress in some systems [25][26][27][28] .…”
Section: Treatment With Mitochondrial Ros Quencher Mitoq Reverses Ementioning
confidence: 77%
See 4 more Smart Citations
“…Studies from our lab and others have identified mitochondrial ROS to be the major cause of cell death in KO MCECs 5,6 . In addition, mitochondrial ROS can also cause lysosomal dysfunction and ER stress in some systems [25][26][27][28] .…”
Section: Treatment With Mitochondrial Ros Quencher Mitoq Reverses Ementioning
confidence: 77%
“…The energy needed for this process is derived from a high density of mitochondria. Corneal endothelial diseases, such as Fuchs Corneal Endothelial Dystrophy (FCED) and Congenital Hereditary Endothelial Dystrophy (CHED), are associated with dysfunctional mitochondria, increased reactive oxygen species (ROS), alterations in cell morphology, function, and eventually cell death [3][4][5][6] . Corneal edema is the main clinical manifestation of FCED and CHED 7,8 , and corneal transplantation is the only available treatment option.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations